2022
DOI: 10.1093/neuonc/noac154
|View full text |Cite
|
Sign up to set email alerts
|

Clinical significance and molecular annotation of cellular morphometric subtypes in lower-grade gliomas discovered by machine learning

Abstract: BACKGROUND Lower grade gliomas (LGG) are heterogenous diseases by clinical, histological, and molecular criteria. We aimed to personalize the diagnosis and therapy of LGG patients by developing and validating robust cellular morphometric subtypes (CMS) and to uncover the molecular signatures underlying these subtypes. METHODS Cellular morphometric biomarkers (CMBs) were identified with artificial intelligence technique from T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 41 publications
0
18
0
Order By: Relevance
“…Over 300 million cellular objects from 1085 diagnostic slides of 1017 TCGA-BRCA patients were recognized and delineated by an unsupervised feature learning pipeline based on SPSD[ 24 ]. Each cellular object was represented with 15 morphometric properties as described in our previous work[ 10 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Over 300 million cellular objects from 1085 diagnostic slides of 1017 TCGA-BRCA patients were recognized and delineated by an unsupervised feature learning pipeline based on SPSD[ 24 ]. Each cellular object was represented with 15 morphometric properties as described in our previous work[ 10 ].…”
Section: Resultsmentioning
confidence: 99%
“…In the past, we followed the same path to define the 12-gene expression prognosis score (GEPS)[ 21 ] and the 15-microbe abundance prognosis score (MAPS)[ 19 ] in BC. Here, we developed the 39-CMB prognosis score (CMPS) using an AI-driven CMB detection technique[ 10 ]. We found that CMPS, MAPS, and GEPS had an independent prognostic value.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…More accurate characterization of tumors may provide insight into novel imaging phenotypes, given the unprecedented demand for genetic properties. With the availability of datasets such as The Cancer Genome Atlas Low Grade Glioma (TCGA-LGG), it is now possible to perform large-scale analyses that are not restricted to one institution [7]. While machine learning methods such as radiomics and deep learning can be expected to provide more accurate diagnostic outcomes than conventional analyses that rely on the human eye, it is still challenging to translate these methods into indicators that can be easily applied in clinical practice.…”
mentioning
confidence: 99%